To your eternity. 11 - Oima, Yoshitoki (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2019)
The Nokkers make a vigorous attack on Renril, but Fushi has found battle-ready allies in Kai, Hairo, and Messar. The sides match each other blow for blow, and exhaustion soon takes its toll on Fushi and the townspeople. Meanwhile, a familiar little girl is resurrected, and makes her way to help her cherished Fu.